2011
DOI: 10.1603/en10126
|View full text |Cite
|
Sign up to set email alerts
|

Inoculating Poultry Manure With Companion Bacteria Influences Growth and Development of Black Soldier Fly (Diptera: Stratiomyidae) Larvae

Abstract: The growth and development of black soldier fly, Hermetia illucens (L.), larvae fed chicken manure inoculated with bacteria isolated from black soldier fly larvae and associated larval feed was evaluated. Four strains of Bacillus subtilis were evaluated. B. subtilis strains S15, S16, S19, were isolated from the gut of black soldier fly larvae. B. natto strain D1 was isolated from the diet fed to black soldier fly larvae. These bacteria were added individually into nonsterile 200 g fresh hen manure at 10(6) cfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
2
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(119 citation statements)
references
References 20 publications
2
104
2
11
Order By: Relevance
“…Jeon et al (2011) reported that a signifi cant factor is amount and composition of bacteria in the digestive tract of the larvae HI. Yu et al (2011) have even proven impact on growth and development of larvae HI a er inoculating poultry manure with bacteria from HI larvae. The actual weight reduction may not be the only indicator of positivity using larvae HI processing biological waste.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jeon et al (2011) reported that a signifi cant factor is amount and composition of bacteria in the digestive tract of the larvae HI. Yu et al (2011) have even proven impact on growth and development of larvae HI a er inoculating poultry manure with bacteria from HI larvae. The actual weight reduction may not be the only indicator of positivity using larvae HI processing biological waste.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that Hermetia illucens larvae are used for reducing weight of food waste (Zheng et al, 2012;Jeon et al, 2011) and for reducing weight of manure Yu et al, 2011;Myers et al, 2008;Newton et al, 2005). For very favourable results, the usage of HI for the treatment of biowaste is discussed not only in states, where the incidence of HI is natural (Diener et al, 2009) but also in states where you will need to use controlled breeding (Holmes et al, 2012), as in the case of Czech Republic.…”
mentioning
confidence: 99%
“…For waste management BSF larvae can be fed with food and market waste (Diener et al 2011;Leong et al 2015;Nguyen et al 2015;Parra Paz et al 2015), animal manure (Li et al 2011b;Myers et al 2008;Sheppard et al 1994;Yu et al 2011), human excreta (Banks et al 2014;Lalander et al 2013) and fish waste (St-Hilaire et al 2007). The importance of a certain moisture level in the feedstock was demonstrated by Furman et al (1959) where moistening chicken manure resulted in significant higher waste reduction.…”
Section: Black Soldier Fly Treatmentmentioning
confidence: 99%
“…Larva BSF mampu hidup dan berkembang dalam berbagai media organik karena sifatnya yang memiliki toleransi pH yang luas (Mangunwardoyo, Aulia, & Hem, 2011). Selain itu, beberapa bakteri yang terdapat di dalam saluran pencernaan larva BSF memiliki kemampuan dalam merombak senyawa organik yang dikonsumsinya (Dong, Chen, Huang, & Feng, 2009;Yu, et al, 2011).…”
Section: Pendahuluanunclassified
“…Selain itu, beberapa bakteri yang terdapat di dalam saluran pencernaan larva BSF memiliki kemampuan dal am merombak senyawa organik yang dikonsumsinya (Dong et al, 2009;Yu et al, 2011).…”
Section: Hasil Dan Bahasan Proksimat Umpan Dan Larvaunclassified